Effect of Surface Sandblasting and Turning on Compressive Strength of Thin 316L Stainless Steel Shells Produced by Laser Powder Bed Fusion - Bharat Mehta; Eduard Hryha; Lars Nyborg; Frederic Tholence; Erik Johansson (Metals, 2021)
This study evaluates the effect of post-manufacturing treatment on the compressive performance of additively manufactured components. The components were thin cylindrical shells with an aspect ratio of 25:1 manufactured using laser powder bed fusion and that were then surface treated by means of sandblasting or turning. The as-printed and subsequently surface treated samples were uniaxially compressed until failure to depict the effect of the surface condition on the compressive mechanical behavior. The results show that as the surfaces became smoother via sandblasting, the average peak strength for buckling load improves negligibly (0.85%), whereas this effect reaches 6.5% upon surface layer removal via turning. Through microstructural investigation and co-relating this with an understanding of processing conditions existing in manufacturing itself, this effect is seen to be linked to contour scanning causing softening of the surface region in a component.